A comparative exploration of a genre set: research article abstracts and introductions across disciplines / Rajasegaran Krishnasamy, Abdul Ghafar Baba and Geraldine De Mello - Rajasegaran Krishnasamy; Abdul Ghafar Baba; Geraldine De Mello (Institute of Research, Development and Commercialization, 2010)
The growth of English for the dissemination of academic knowledge requires researchers to be fluent in the conventions of academic discourses. Over the last two decades, genre has increasingly taken prominence in aiding teachers in second language classrooms. In this study, genre analysis is discussed and its potential as a tool for enhancing the learning of writing in the disciplines. This study aims to discover the structure of the abstract and introduction in two disciplines in the social sciences, then discern the relationship between these genres in each discipline, before comparing them across disciplines. The study applies the move analysis to examine the genre set in a corpus, comprising 60 research article abstracts and introductions in Educational Psychology and Environmental Psychology published between 2005 and 2007 from Contemporary Educational Psychology, and the Journal of Environmental Psychology respectively. The knowledge should contribute to an understanding of the discourse in research articles and reinforce or challenge how well moves analyses gives an in-depth perspective on the formation of both abstract and Introduction in research. The rhetorical structure to be created could simplifying academic writing, facilitating novices to the discourse community of researchers in Educational Psychology and Environmental Psychology. The results of this study could provide a basic template for the structuring of interdisciplinary research abstracts and introductions which may assist readers who perceive they have difficulty in understanding research articles, as well as to less experienced writers who require assistance when writing for publication to better meet the expectations and demands of international academia.